SUSCEPTIBILIDADE DOS ECOSSISTEMAS CONTINENTAIS DA BAIXADA MARANHENSE AOS EFLUENTES ATMOSFÉRICOS LIBERADOS POR SÃO LUÍS MA: ESTUDOS DE CASO DE PINHEIRO E VIANA - Silva, Richardson Gomes Lima da (2006)
In Maranhao, studies on the atmospheric chemistry are scarce, with only one record for the region of Lagoa do Caco, in First Cross. Although still a developing city, with moderate urban growth and incipient industrialization rate, the implantation of the steel complex in St. Louis - as the Aluminum Industry of Maranhão (ALUMAR) and the pellet plant and production of steel plates (in installation phase) of Companhia Vale do Rio Doce - in the region increases the potential for emission of particles and gases into the atmosphere, which may contribute to altering the characteristics of rain and the ecological balance of sensitive areas like the low lands due geographical location and weather conditions this state. These circumstances underscore the need to verify the potential emissions released by the urban-industrial activity on the island have on the ecosystems of the lowlands. Most of the regions studied in this work (Panaquatira, Cashew and Pine) has the major influence on rainwater ions of marine origin, a situation already expected due to location near the coast. The sampling points located in St. Louis (Panaquatira, Cashew and Coconut) had acid deposition events in 46.57% of samples. However, when considering the value 5.0 as the lower limit of pH for rainwater acidified by natural processes, only 16.44% of the samples showed high acidity, Cashew and Coconut, indicating that the processes of urban-industrial St. Louis would negatively affect the pH of rainfall in these regions. Among the ions, fluoride had its highest concentrations in Cashew and Coconut, possibly due to their location close to Vale do Rio Doce and ALUMAR respectively emitting industries by nature potential of this element to the atmosphere. Although they presented isolated events of acid deposition, and Viana Pinheiro received predominantly deposition events with pH higher than expected (5.6) for natural environments. This may have its origin in the high levels of ammonia found in samples of rain in these regions, probably due to extensive breeding of animals, which release large quantities of this compound into the atmosphere through their droppings. The soils in the low lands showed a great susceptibility to acidity from the calculation of critical load part (CCP). Although not occurring phenomena of acid deposition in these locations, the high levels of ammonia can be harmful to the soil, as ammonium salts, formed from the reaction of NH4 + with acidic compounds in the atmosphere, may release more H + than acid deposition itself.